Fraccionamiento y cuantificación de la materia orgánica en andisoles bajo diferentes sistemas de producción (2013)
In Andisols of the Cajibio municipalities, Cauca department and Sevilla, Valle del Cauca department,Colombia, the effect of soil use with forest Systems was evaluated, guadua (Guadua angustifolia K.), coffee crops (Coffea arábiga Caturra cultivar), with total sun exposure, shaded with guamo (Inga sp), walnut tree shadow and Brachiaria pasture over different organic matter compounds. Soil samples were taken in a Typic Melanudand located in the Cauca department to 1740 m.a.s.n. and a Typic Haplustand in Sevilla, Valle del Cauca, department to 1660 m.a.s.n. Soils were characterized by determination of physical and chemical properties; humic substances were obtained with sequential extraction solutions tetraborate, pyrophosphate and sodium hydroxide prior granulometric separation by wet sieving. Then purified and characterized humic and fulvic acids by different analytical and spectroscopic techniques. Were found significantly differences in the properties evaluated by the effect of the use and soil type. The higher acidity was performed at the Typic Melanudand (pH and lt; 5.6). Typic Haplustand shows abrupt changes in going from slightly acidic pH (6.2) to highly acidic ( and lt; 5.5) by the change in land use. Typic Melanudand had higher organic carbon content. The humus was highert han fresh in both soils, yields on extraction of humic substances changed with soil use and content of humic acids was higher than the fulvic acids. Relations among both compounds showed differences E4/E6 use and soil type for humic and fulvic acids. Hydrophobicity indices were higher than 1.0 than humic acids and fulvic acids lower than 1.0. Acid fulvic performs a greatest condensation degrees in the Typic Melanudand soil.